Messengers in the structure of media preferences of the national audience - Postalovsky, Alexander V. (Journal of the Belarusian State University. Sociology, 2021)
The presented article is devoted to the analysis of the place and role of messengers in the structure of media consumption of the audience and the national information field as a whole. Based on the data of a mass survey of the population conducted by the Center of Sociological and Political Studies of the Belarusian State University in 2020, the most popular instant messengers are identified, the place of these resources among traditional media and social media space is determined, and the features of media consumption practices are considered. As part of the study, it was possible to establish that instant messengers, in particular, the Telegram resource are used for their intended purpose both as a communication channel and as a channel for disseminating mass information. The results obtained allow us to conclude that the popularity of instant messengers relative to other segments of the national information field will continue to grow.
Keywords: mass information; instant messengers; information field; media consumption; Telegram